Estudo da implementação do Lean Construction com apoio do BIM - Fermiano, Lana Maria Aragão (Universidade Federal de São Carlos, 2022)
The Civil Construction Industry is characterized as a sector with a complex production flow. The diversity of stages, even in small projects, produces a large informational input that, based on the current model for organizing and managing project information - based on 2D - has the potential to generate divergences, omissions, duplications or project doubts that reflect in production stages. Besides the lack of integration and communication of the current structure that can drive delays, additional costs and production errors throughout the life cycle of a construction project. Therefore, Lean Construction and Building Information Modeling (BIM) have the potential to solve some of the most recurrent problems in the Architecture, Engineering, Construction and Operation (AECO) industry. Thus, this paper aims to analyze the main Lean Construction tools that contribute to the conduct of construction processes and can be catalyzed through the BIM methodology. To this end, a Systematic Literature Review (SLR) was conducted in order to collect the main concepts and conclusions already existent on the proposed theme and a Case Study was analyzed in the execution phase of the Last Planner System (LPS) and prefabricated systems, and such implementations converge with the Lean Construction principles. From the RSL, it was possible to conclude that BIM can act as a Lean catalyst methodology due to its collaboration, coordination, facilitated communication, 3D visualisation and 4D simulation functionalities, improving the processes conduction and the product result. In this context, a BIM implementation proposal was carried out with the objective of catalyzing Lean Construction in the Case Study.
Study of the implementation of Lean Construction with the support of BIM
Keywords: Pré-fabricados; BIM; Modelagem de informação da construção; Lean construction; Last planner system; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL